KAJIAN PERBANDINGAN TINGKAT PENGEMBALIAN dan RISIKO ANTARA INVESTASI EMAS dan SAHAM SYARIAH - Tais Khuron (Signifikan: Jurnal Ilmu Ekonomi, 2015)
The objective of this research is to compare the return and risk between gold and shariah stocks. The measurement using the actual return between gold and shariah stocks, actual risk using standard of deviation between gold and shariah stocks, and the correlation between return and risk in gold and shariah stocks. The result shows that the stock’s performance is better than gold in actual return, but gold has low risk if compare with the stocks.  There are five stock that have a positive correlation with gold, such as: INTP, KLBF, SMGR, UNTR, and UNVR. TLKM stocks is the only one stock that has a negative correlation with gold.DOI: 10.15408/sjie.v4i1.2294